The indications for and timing of surgery for diverticular disease - Lock, Johan Friso; Galata, Christian; Reißfelder, Christoph; Ritz, Jörg-Peter; Schiedeck, Thomas; Germer, Christoph-Thomas (Deutsches Ärzteblatt, 2020)
Diverticular disease is one of the most common gastrointestinal conditions and diverticulitis is an important differential diagnosis of acute abdominal pain. An analysis of the diagnosis data of the German Federal Statistical Office for 2016...